A Catalogue of Tibetan Texts Kept at M. K. Ciurlionis National Museum of Art (Kaunas, Lithuania) - Kugevičius, Algirdas (Acta Orientalia Vilnensia, 2004)
More than hundred different Tibetan texts are kept at M. K. Čiurlionis National Museum of Art (Kaunas, Lithuania). This catalogue in itself is the summary of the collection of Tibetan texts. It is designed not only to ease finding of texts but also to contribute a drop to the general knowledge of what old treasures of the East lie in the darkness of underground of Lithuanian museums in these modem times when halls of museums are often occupied by expositions expressing mostly the Western confusion of mind and mind-games for “artistic” and “intellectual” elite.The texts are grouped here according to the traditional Tibetan and Buddhist fields of knowledge. So one interested in some of those fields can easily find needed texts (looking at contents, at descriptions of texts and fixing their inventorial numbers). Then with the permission of the authorities of the Museum one can study them at the Arts and Crafts Department where they are kept.